Pengembangan Literasi Digital dalam Pembelajaran PAI untuk Mencegah Disinformasi Agama Pada Generasi Z - Abdul Halim Rais (STAI Kuala Kapuas, 2026)
The rapid development of digital technology has transformed how Generation Z—digital natives who rely heavily on online platforms—access and understand religious information. However, this accessibility has also increased their exposure to religious disinformation and intolerant narratives. This study aims to explore the development of digital literacy in Islamic Religious Education (PAI) as a preventive measure against the spread of religious disinformation among Generation Z. Using a descriptive qualitative approach, the research examines how teachers and students integrate digital literacy into PAI learning and how it strengthens students’ ability to verify and interpret online religious content critically and ethically. The findings indicate that digital literacy in PAI must extend beyond technical skills to include critical thinking, ethical responsibility, and Islamic values such as tabayyun (information verification). Effective strategies include improving teachers’ digital competence through continuous training, integrating digital literacy into the curriculum, fostering students’ digital ethics, providing equitable access to digital infrastructure, and conducting continuous evaluation. Strengthening digital literacy in PAI not only enhances students’ religious understanding but also builds resilience against misinformation, thereby nurturing a generation that is religiously moderate, critical, and wise in digital interactions.